1976
DOI: 10.1093/jnci/56.4.735
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immunity Induced by Preimmunization With BALB/c Mouse Myeloma Protein2

Abstract: Prior sc immunization of BALB/c mice with 1 mg isolated M component of MOPC-11 mouse myeloma resulted in significant relative immunity to subsequent sc or ip challenge with 10(4) living cells from the same plasmacytoma. However, challenges of 10(5) and 10(6) tumor cells overcame immune status engendered by preimmunization with M component. Despite evidence for the specificity of the immunity induced by one isolated M component as opposed to another, no clear cytotoxic antibody, cell-mediated tumor-cell lysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 4 publications
3
13
0
Order By: Relevance
“…Sirisinha and Eisen (1) and Lynch et al (2) were the first to demonstrate that syngeneic tumor-derived Ig could induce the production of antibodies directed against the MOPC-315 idiotype, as well as induce idiotype-specific resistance to tumor growth. The induction of idiotype-specific immunity by active immunization with tumor-derived Ig has subsequently been demonstrated for a number of myeloma (3)(4)(5)(6) and B-cell lymphoma or leukemia models (7)(8)(9)(10), usually requiring complete Freund's adjuvant or conjugation to a strongly immunogenic carrier protein. In addition, our pilot studies in human patients with lymphoma and myeloma have demonstrated that idiotype-specific immunologic responses can be induced by immunization with autologous tumor-derived idiotypic Ig (Id), conjugated to keyhole limpet hemocyanin (KLH) (11,12).…”
mentioning
confidence: 99%
“…Sirisinha and Eisen (1) and Lynch et al (2) were the first to demonstrate that syngeneic tumor-derived Ig could induce the production of antibodies directed against the MOPC-315 idiotype, as well as induce idiotype-specific resistance to tumor growth. The induction of idiotype-specific immunity by active immunization with tumor-derived Ig has subsequently been demonstrated for a number of myeloma (3)(4)(5)(6) and B-cell lymphoma or leukemia models (7)(8)(9)(10), usually requiring complete Freund's adjuvant or conjugation to a strongly immunogenic carrier protein. In addition, our pilot studies in human patients with lymphoma and myeloma have demonstrated that idiotype-specific immunologic responses can be induced by immunization with autologous tumor-derived idiotypic Ig (Id), conjugated to keyhole limpet hemocyanin (KLH) (11,12).…”
mentioning
confidence: 99%
“…Compared with isotype control antibody treatment, in all 10 patients, cytokine induction was at least partially inhibited by either anti-HLA class I or class II blocking antibodies, suggesting 4 S. Neelapu and L. Kwak, unpublished observations. Fig.…”
Section: Resultsmentioning
confidence: 82%
“…These data were consistent with results from our previous studies with Id vaccines in FL patients, in which we generally observed type I but not type II tumorspecific cytokine responses. 4 To test specificity of the T-cell responses, postvaccine PBMCs were cocultured with either sCD40Lt-activated autologous normal B cells or activated tumor cells in parallel. Significant production of cytokines (IFN␥, GM-CSF, and/or TNF-␣) was observed only in response to autologous tumor cells, but not normal B cells, in all 10 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, passive transfer of immune serum did not protect against tumor challenge, and thymus-derived idiotype-specific T helper cells were clearly required to develop protective tumor immunity [53, 54]. Similar results were obtained with the MOPC-11 tumor, although dominant effector mechanisms could not be identified [55]. In contrast, immunization of mice against the idiotype of the murine 141 lymphoma suggested that a protective immune response could also be primarily cell-mediated [56].…”
Section: Animal Models Of Vaccination Against Malignant Lymphomamentioning
confidence: 83%